The Future of Social Policy—Changing the Paradigm. Issue 1 (12th January 2015) - Piachaud, David
Abstract: The future of the social state is, throughout the world, uncertain, but, as Piketty argues, it is of the utmost importance. The dominant paradigm for thinking about social policy both in terms of government action and academic analysis has been the social service model, as exemplified in the work of Richard Titmuss. In the West, there has been a growing crisis in social policy. Demand for social services has increased for demographic, economic, technological and political reasons; supply has been constrained for economic and political reasons. There is a growing realisation that social services are only one, often small, factor in determining social outcomes. Yet the social service model focuses largely on inputs. It is argued, with examples from across the life cycle, that the paradigm for social policy needs to change from focusing on inputs to focusing on the intended outcomes or social goals.